Effects of Breeder Age on Genetic Parameter Estimates of Slaughter and Carcass Traits in Japanese Quail - Gurcan, Eser Kemal; Narinc, Dogan; Kaplan, Selcuk (International Journal of Scientific Research and Management (IJSRM), 2018)
This study aimed to determine the phenotypic values of the slaughter and carcass traits in the flocks of quails obtained when a flock of parent quails were at 12, 16, and 20 weeks of age and to estimate the heritabilities and the genetic correlations for these traits. For this purpose, a total of 1,346 Japanese quails were slaughtered at 8 weeks of age, and their slaughter weights as well as carcass, breast, leg, and abdominal fat weights and ratios were determined. Differences in all traits were detected between female and male quails (P